A cultura indígena nos museus da cidade de Belo Horizonte - Aline Vicentina Santos Barroso (2017)
This study investigates the presence of the Brazilian indigenous culture in the city of Belo Horizonte's museums, in Minas Gerais state. The purpose of this research was to create an Interpretative itinerary (educational product) with izi. TRAVEL application for exploring objects that belong or refer to the Brazilian indigenous culture and have been part of the permanent exhibition in Belo Horizonte museums since 2015. The itinerary entitled Between Streets and Villages: the Indigenous Culture in Belo Horizonte Museums is composed of six attractions: first, Streets and Ethnicities: the Indigenous Peoples in Minas Gerais; second, Language; third, Indigenous Peoples Science; fourth, The Labor; fifth, Citizenship and sixth, The Indigenous Childhood. Its main purpose is to be used by basic education teachers no matter what they teach. It is aimed that this educational product inspire new discussions, reflections and knowledge acquisition in schools on the matter of Brazilian indigenous culture and the Law 11.645/2008 by means of promoting museum collections, artifacts and exhibitions in Belo Horizonte museums. Initially, the research was carried-out in thirty-nine (39) museums in which only seven (7) of them hold objects in permanent exhibitions that belong or refer to the Brazilian indigenous culture. Those are: Toy Museum (Museu dos Brinquedos), Arts and Crafts Museum (Museu de Artes e Ofícios), Mineiro Museum (Museu Mineiro), Belo Horizonte Audio-visual Museum (Museu da Imagem e do som de Belo Horizonte), UFMG Place of Knowledge (Espaço do Conhecimento UFMG), Labour Court Memory Center (Centro de Memória da Justiça do Trabalho), Historic Cartography Reference Center (Centro de Referência em Cartografia Histórica). The methodology consisted in a desk research of the objects, documents, photographs and videos found in the museums.The content analysis methodology was used to evaluate the discourse of the seven (7) museums missions. The result indicates that the indigenous issues are addressed in Belo Horizonte museums, but are not put in a prominent place. Many exhibitions portray the indigenous peoples from the Colonial and Imperial period. However, Belo Horizonte museums need to expand the discussions about ethnic and cultural diversity of both ancient and contemporary indigenous peoples. As museums are places for informal education, they have great potential tohost discussion on the indigenous issues and implement the law 11.645/2008.